(untitled) - Hendry, Joy (New York, 1987)
As Japan enters the 21st century with a new emperor, this title continues to be an indispensable guide through often enigmatic and historical idiosyncrasies of Japanese culture and politics that are often confusing to the outsider. Fully updated, revised and expanded, this is a welcome new edition of this best-selling book that has provided an accessible and readable introduction to Japanese society over the years. Now containing some of the most up-to-date information on Japanese cultural and political trends, this essential title includes timely information on the latest social developments, customs, rituals, business culture, medicine and arts.
Keywords: Japan; Social conditions